Clear Cell Papillary Cystadenoma of the Ovary Masquerading as Metastatic Clear Cell Renal Cell Carcinoma: A Case Report and Review of the Literature. (May 2021) - Sharma, Aarti E.; Hamedani, Farid Saei; Barroeta, Julieta E.; Pytel, Peter; Bennett, Jennifer A.; Lastra, Ricardo R.
Abstract : Clear cell papillary cystadenoma of the epididymis is an uncommon benign neoplasm, usually seen in patients with von Hippel-Lindau disease. Morphologic and immunohistochemical examination aid in distinguishing clear cell papillary cystadenoma from malignant histologic mimics including low-grade mesothelial proliferations and metastatic clear cell renal cell carcinomas. Analogous lesions have been described in the female genital tract, often posing diagnostic challenges due to their low incidence. Here, we present the difficult diagnostic aspects of the first case of clear cell papillary cystadenoma involving the ovary, including the salient immunohistochemical, ultrastructural, and molecular characteristics.